GAMBARAN STRUKTUR MIKROANATOMI UTERUS MENCIT ( Mus musculus L) SETELAH PEMBERIAN FRAKSI n-HEKSANA DAN FRAKSI ETIL ASETAT KULIT BATANG DURIAN (Durio zibethinus Murr) - Hikmah Hikmah; Rusmiati Rusmiati; Heri Budi Santoso (Universitas Lambung Mangkurat, 2009)
The selection of modern contraceptive methods, particularly associated with hormonal way can cause side effects, for the most people, especially rural communities are still using natural contraception, one of them is using part of durian plantation. This research was conducted to determine the structure microanatomy picture of mice’s uterus after the fraction n-hexane and ethyl acetate fraction of the bark of durian. This research using completely randomized design with 3 treatments of control, the fraction of nhexane and ethyl acetate fraction with the repetition of 5 times for each treatment. Multiple comparison test using Duncan's test showed that n-hexane fraction and ethyl acetate fraction of bark of durian affects the thickness of mice’s uterus, that is the depletion of endometrium layer and myometrium layer. Depletion layer of the endometrium and myometrium is because bark of durians contains compounds antifertility are alkaloids, flavonoids, tannins, saponins and triterpenoid.